Teachers' Self-Efficacy during the COVID-19 Pandemic in Greece: The Role of Risk Perception and Teachers' Relationship with Technology - Eleni Andreou; Christina Roussi; Stella Tsermentseli; Laura Menabò; Annalisa Guarini (MDPI AG, 2022)
The COVID-19 pandemic has led to a sudden and radical transition from face-to-face to online teaching across the globe. This shift has required teachers to quickly adapt their educational practices, which has had an impact on their perceived self-efficacy. The limited literature on the impact of COVID-19 on teachers' self-efficacy (TSE) has focused mostly on online teaching. The purpose of this study was to investigate TSE in both face-to-face and distant learning environments amid the COVID-19 pandemic. It also aimed to explore the impact of teachers' relationship with technology and COVID-19 risk perception on their TSE. The sample was composed of 290 pre-service and in-service teachers from Greece who completed an online self-report survey. Results showed that pre-service teachers reported higher levels of TSE than in-service teachers, especially in distance learning environments. COVID-19 risk perception was not a significant predictor of TSE. By contrast, higher scores in self-assessed skills of the pedagogical applications of technology predicted TSE in both instructional settings. The present findings confirm the importance of promoting technological skills to enhance the self-efficacy of schoolteachers in both traditional and virtual instructional settings, regardless of the crisis due to the COVID-19 pandemic.